Selection of common bean progenies for fall and winter planting in south Minas Gerais, Brazil - Santos, João B. dos; Ramalho, Magno A. P. (Pesquisa Agropecuaria Brasileira, 2014)
Eight segregant common bean (Phaseolus vulgaris L.) populations were evaluated through the "massal" test (bulk) in the winter seasons of 1982-84, in the south region of Minas Gerais, Brazil, for the purpose of selecting the progenies best adapted to those conditions. In 1985, 450 plante characterized by both high seed yield and marketable seed type were selected, procuring the most fit. Through successive selection cycles from 1986 to 1988, the thirteen most promising progenies for winter cultivation were determined by observing the most cold tolerant, shrubby, the highest productive and marketable seed type. The progenie ESAL 572, that has a 100-seed weight of 25 g and purple seed color, showed to be adapted to the improved environmental conditions. ESAL 603, with 100-seed weight around 22 g, purple seed colour (similar to Carioca) showed to be well adapted to the intermediate environmental conditions. In addition, both ESAL 572 and 603 progenies showed the highest seed yield.